STAKEHOLDERS MAPPING DALAM PENGEMBANGAN PARIWISATA DI DESA WISATA GIRIMULYO KABUPATEN KARANGANYAR - Devi Martini; Satria Aji Imawan (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2026)
Girimulyo Tourism Village in Karanganyar Regency has natural, cultural, and culinary tourism potential, but its development remains suboptimal because it is still in the pioneering stage and faces challenges in governance, promotion, integrated tour packaging, and supporting facilities. This study aims to identify the stakeholders involved in tourism development in Girimulyo Tourism Village and analyze their positions and roles based on power-interest theory. The study employed a descriptive qualitative approach in Girimulyo Village, Ngargoyoso District, Karanganyar Regency, with data collected through semi-structured interviews, observation, and document review, and validated through source and technique triangulation. The findings show that nine stakeholders from the government, business, and community sectors are involved and can be classified into three groups: (a) primary stakeholders, including Pokdarwis Girimulyo, Karang Taruna, local businesses and UMKM, and the village community; (b) key stakeholders, consisting of the Girimulyo Village Government and Pokdarwis; and (c) secondary stakeholders, including Disparpora, Dispermades, BUMDes, and PT Asuransi Sinar Mas. In the power-interest matrix, the Village Government and Pokdarwis are categorized as players, Disparpora as a context setter, local businesses and UMKM, Karang Taruna, and the community as subjects, and Dispermades, BUMDes, and PT Asuransi Sinar Mas as crowd.